1976
DOI: 10.3177/jnsv.22.339
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic response to a pantothenic acid deficient diet in humans.

Abstract: SummaryThe responses of human subjects to a low pantothenic acid test diet and to the same diet supplemented with 10mg pantothenic acid daily for 63 days were observed. Pantothenic acid in urine and blood and also nitrogen balance were used as criteria for nutritional evaluation. The mean daily urinary pantothenic acid excretion decreased from 3.05 to 0.79mg in male adult subjects fed a pantothenic acid deficient diet and increased from 3.95 to 5.84mg in 4 subjects fed a 10mg supplement ed diet from the beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…The significant positive correlation between dietary vitamin intake and urinary excretion levels has been reported previously in the literature (48)(49)(50). In the present experiment, the urinary excretion levels were lower in the 3rd trimester and lactating women than in control and 2nd trimester women (Fig.…”
Section: Pantothenic Acidsupporting
confidence: 70%
“…The significant positive correlation between dietary vitamin intake and urinary excretion levels has been reported previously in the literature (48)(49)(50). In the present experiment, the urinary excretion levels were lower in the 3rd trimester and lactating women than in control and 2nd trimester women (Fig.…”
Section: Pantothenic Acidsupporting
confidence: 70%
“…Inadequate intake of vitamins typically causes a reduction in the concentration of vitamins in the cells and body fluid. So far, the most commonly used procedure to assess the nutritional status of B-group vitamins has been measurement of the urinary levels of these vitamins ( 9 13 ) . Our research team ( 14 – 21 ) and other investigators ( 22 27 ) have shown that the urinary excretion of B-group vitamins provides an indication of the recent dietary intakes of these vitamins.…”
mentioning
confidence: 99%
“…In both studies, urinary excretion was observed to be lower (30-60 %) than intake at all doses tested, except at the lowest intake of 2.8 mg/day, at which the mean urinary excretion was 3.2 mg/day. Upon depletion with a pantothenic acid-free diet for nine weeks, urinary excretion decreased to 0.79 ± 0.17 mg/day in six men compared with a urinary pantothenic acid excretion of 3.05 ± 1.20 mg/day at baseline at intakes of 6.45 mg/day (range 4.85-8.16 mg/day) (Fry et al, 1976).…”
Section: Biomarkersmentioning
confidence: 85%
“…Pantothenic acid is excreted in urine, after hydrolysis of CoA in a multistep reaction. In a few groups of healthy subjects, average daily urinary excretion of pantothenic acid was observed to range between about 2.0 and 3.5 mg/day in children and adolescents (Schmidt, 1951;Kathman and Kies, 1984;Eissenstat et al, 1986) and between about 2.0 mg and 4.0 mg/day in adults (Schmidt, 1951;Fox and Linkswiler, 1961;Fry et al, 1976;Kathman and Kies, 1984;Song et al, 1985). Urinary excretion of pantothenic acid is positively correlated with pantothenic acid intakes (see Section 2.3).…”
Section: Function Physiology and Metabolismmentioning
confidence: 99%